Indoor hydroponics farming system monitoring via internet of things (IoT) - Goh, Yee Sin (2023)
Hydroponics is a soilless farming method that provides plants exactly what they need when they need it. This project aimed to develop a smart hydroponic monitoring system using Internet of Things (IoT) technology. The system was designed to measure important environmental parameters, including water temperature, humidity, surrounding temperature, pH value and electrical conductivity of nutrient solution, using various sensors connected to a microprocessor. The data were then displayed on a dashboard in Cayenne, enabling continuous monitoring of the growing environment of crops. Two experiments were conducted on the built prototype to determine the optimal fertilizer volume and frequency for Amaranthus tricolor (Bayam Hijau), and the results showed that 8ml of fertilizer, applied twice during a 10-day growing cycle, was the most effective. The productivity of hydroponic agriculture systems was evaluated through a meta-analysis that estimated global vegetable crop yields based on data gathered from relevant literature. Additionally, the effect of 2 criteria of the growing system on hydroponic crop yields, namely growing orientation (vertical vs. horizontal) and the condition of the growing environment (controlled environment vs. open air) were studied. Through the meta-analysis, hydroponics was found out to be more suitable for “Anise, badian, fennel & coriander”, “Chillies & peppers” and “Cucumbers & gherkins”. In terms of growing environment, controlled environment led to a higher hydroponic crop yields than open air agriculture for all the significantly affected crop categories. However, an overall trend regarding the best growing orientation could not be observed. Overall, this project provides valuable insights into the optimization of hydroponic farming for enhanced crop yields and sustainable agriculture.